Effectiveness and Efficiency Improvement of Local Content at the Upstream Oil and Gas Industry by Employing Live Verification Method - Rama Atyasa Y; Supriyatno Supriyatno; Alva Edy Tontowi (International Conference on Economic Business and Social Science, 2025)
This study examines the impact of live verification as an innovative approach to local content verification at PT Pertamina Hulu Energi (PT PHE), by comparing its efficiency and effectiveness against conventional verification methods. By analyzing 207 contracts (verified in 2022-2024), this study documents the transition from conventional verification (50 contracts in 2022) to live verification (71 contracts in 2023, 77 contracts in 2024), with little retention of conventional methods (4 and 5 contracts respectively). By applying Business Process Re-engineering (BPR), this study aims to demonstrate significant process simplification, reducing verification steps from 9 steps to 6 steps and consolidating 4 steps into 1 step. Furthermore, statistical tests were conducted to validate the significant changes before and after the live verification method was implemented. Including homogeneity test and one-way ANOVA was chosen because it was considered suitable by involving three independent variables (2022, 2023, 2024) and the dependent variable which is verification time (SLA). Statistical validation through descriptive frequency analysis showed that the average verification processing time in 2023 (25,45 working days) and 2024 (14,55 working days) was getting closer to the ideal benchmark. Furthermore, homogeneity testing and one-way ANOVA confirmed a statistically significant improvement, with significance values of <0.001 (by mean) and 0.001 (<0.05 for ANOVA), indicating a substantial reduction in SLA post-implementation. Then the implementation of verification is measured by the effectiveness test and the results show that in 2023 & 2024 the live verification process is considered effective with a cumulative achievement rate of 32%, and in terms of efficiency it is considered efficient with a cumulative achievement rate of 87,18%. This live verification method can be an effective solution to speed up the local content verification process and help solve problems in the local content verification process. The findings underscore live verification as a transformative strategy, improving process agility, cost efficiency, and compliance performance. This research contributes to the production process literature by offering a data-driven framework for process optimization, as well as actionable insights for energy sector policymakers and potential scalability in the context of global supply chain compliance.